Ion transport peptide splice forms in central and peripheral neurons throughout postembryogenesis of Drosophila melanogaster. - Dircksen, H.; Tesfai, L.K.; Albus, C.; Nässel, D.R. (Journal of Comparative Neurology, 2008)
Ion transport peptides (ITPs) belong to a large arthropod neuropeptide family including crustacean hyperglycaemic hormones and are antidiuretic hormones in locusts. Because long and short ITP isoforms are generated by alternative splicing from a single gene in locusts and moths, we investigated whether similarly spliced gene products occur in the nervous system of Drosophila melanogaster throughout postembryogenesis. The itp gene CG13586 was reanalyzed, and we found three instead of the two previously annotated alternatively spliced mRNAs. These give rise to three different neuropeptides, two long C-terminally carboxylated isoforms (DrmITPL1 and DrmITPL2, both 87 amino acids) and one short amidated DrmITP (73 amino acids), which were partially identified biochemically. Immunocytochemistry and in situ hybridization reveal nine larval and 14 adult identified neurons: four pars lateralis neurosecretory neurons, three hindgut-innervating neurons in abdominal ganglia, and a stage-specific number of interneurons and peripheral bipolar neurons. The neurosecretory neurons persist throughout postembryogenesis, form release sites in corpora cardiaca, and invade corpora allata. One type of ITP-expressing interneuron exists only in the larval and prepupal subesophageal ganglia, whereas three types of interneurons in the adult brain arise in late pupae and invade circumscribed neuropils in superior median and lateral brain areas. One peripheral bipolar and putative sensory neuron type occurs in the larval, pupal, and adult preterminal abdominal segments. Although the neurosecretory neurons may release DrmITP and DrmITPL2 into the haemolymph, possible physiological roles of the hindgut-innervating and peripheral neurons as well as the interneurons are yet to be identified.